The climate change mitigation effect of bioenergy from sustainably managed forests in Central Europe. Issue 3 (7th February 2020) - Schulze, Ernst Detlef; Sierra, Carlos A.; Egenolf, Vincent; Woerdehoff, Rene; Irslinger, Roland; Baldamus, Conrad; Stupak, Inge; Spellmann, Hermann
Abstract: We compare sustainably managed with unmanaged forests in terms of their contribution to climate change mitigation based on published data. For sustainably managed forests, accounting of carbon (C) storage based on ecosystem biomass and products as required by the United Nations Framework Convention on Climate Change is not sufficient to quantify their contribution to climate change mitigation. The ultimate value of biomass is its use for biomaterials and bioenergy. Taking Germany as an example, we show that the average removals of wood from managed forests are higher than stated by official reports, ranging between 56 and 86 mill. m 3  year −1 due to the unrecorded harvest of firewood. We find that removals from one hectare can substitute 0.87 m 3  ha −1  year −1 of diesel, or 7.4 MWh ha −1  year −1, taking into account the unrecorded firewood, the use of fuel for harvesting and processing, and the efficiency of energy conversion. Energy substitution ranges between 1.9 and 2.2 t CO2 equiv.  ha −1  year −1 depending on the type of fossil fuel production. Including bioenergy and carbon storage, the total mitigation effect of managed forest ranges between 3.2 and 3.5 t CO2 equiv.  ha −1  year −1 . This is more than previously reported because of the full accounting of bioenergy. Unmanaged nature conservation forests contribute via C storage only about 0.37 t CO2 equiv.  ha −1  year −1 to climate change mitigation. There is no fossil fuel substitution. Therefore, taking forests out of management reduces climate change mitigation benefits substantially. There should be a mitigation cost for taking forest out of management in Central Europe. Since the energy sector is rewarded for the climate benefits of bioenergy, and not the forest sector, we propose that a CO2 tax is used to award the contribution of forest management to fossil fuel substitution and climate change mitigation. This would stimulate the production of wood for products and energy substitution. Abstract : National wood balances underestimate the use of wood for bioenergy. Removals of wood from forests are higher than officially recorded. Since storage of biomass in forests has an upper limit, and since the product pool is transient, it is mainly the use of energy in wood that contribute to climate change mitigation. Annual wood harvest per hectare of forest substitutes almost 900 L diesel or 7.4 MWh. This is equivalent up to 3.5 t CO2 of saved emissions. However, forestry is not rewarded for this effort. When taking forests out of management, this contribution to climate change mitigation is lost. The graphical abstract shows the allocation and use of assimilated carbon in managed and unmanaged forests.